Standar Persiapan Pendidikan dan Pelatihan (Diklat) (Studi Kasus di Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Tengah) - Ajatul Ajatul; Abdul Gofur (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of this study is to determine the standard of preparation of education and training in the BPSDM institution of Central Kalimantan Province. What preparations are made by the Central Kalimantan Province BPSDM institution in preparing or planning training activities. The research method used in this research is qualitative with data collection techniques through observation, interviews and documentation. The research was conducted at the Central Kalimantan Province BPSDM office. The results of this study indicate that the standard of training preparation carried out by the Central Kalimantan Province BPSDM institution is very structured starting from planning activities, analyzing needs, determining training objectives, administrative preparation, educational preparation and organization .